Oyster Mussels (Crassostrea gigas) Analys Financial Feasibility (Case Study in Seishin Company) in Hyogo, Japan - Herman, Adam; Ihsan, Yudi Nurul; Maulina, Ine (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
Japan is known as one of the largest oyster cultivitation in the world. This research aims to analyze the financial feasibility of prospects of cultivitation oyster in Sakoshi, Hyogo prefecture, Japan. The analysis of investment evalution criteria in this study based on financial analysis methods which include, investments cost, operasional costs, Revenue Cost Ratio(R/C) and Break Even Point (BEP). To analyza financial feasibility, investment assessment criteria are used including Net Present Value (NPV), Internal Rate Return (IRR), Net Benefit Cost Ratio (Net B/C) and Payback Period (PP). Based on data analysis, it was obtained that the R/C value was 2.154 and Break Even Point was 3.421 kg. In the calculation of financial feasibility analysis, NPV value was obtained at ¥ 96,788,973, IRR value of 83%, Net B/C value of 2.154 and the Paypack Period for 1.17 years. Base from results of this research, oyster cultivation in Sakoshi, Hoyogo Prefecture, Japan is very feasible and profitable to do and develop in the future.